Event‐Related Potential Responses to the Acute and Chronic Effects of Alcohol in Adolescent and Adult Wistar Rats. (31st January 2014) - Ehlers, Cindy L.; Desikan, Anita; Wills, Derek N.
<x xml:space="preserve">Abstract</x> Background This study explored the hypothesis that adolescent ethanol (EtOH) exposure may cause long‐lasting changes in EtOH sensitivity by exploring the age‐related effects of acute alcohol on intoxication and on event‐related potential (ERP) responses to acoustic stimuli in EtOH‐naïve adolescent and adult male Wistar rats and in adult rats that were exposed to chronic EtOH/control conditions during adolescence. Methods EtOH‐naïve adolescent (postnatal day 32 [PD32]) and adult male rats (PD99) were included in the first study. In a second study, rats were exposed to 5 weeks of EtOH vapor (blood EtOH concentrations at 175 mg%) or air from PD24 to 59 and allowed to mature until PD90. In both studies, rats were implanted with cortical recording electrodes, and the effects of acute EtOH (0.0, 1.5, and 3.0 g/kg) on behavioral and ERP responses were assessed. Results Adolescents were found to have higher amplitude and longer latency P3a and P3b components at baseline as compared to adult rats, and EtOH was found to produce a robust dose‐dependent increase in the latency of the P3a and P3b components of the auditory ERP recorded in cortical sites in both adolescents and adults. However, EtOH produced significantly larger delays in P3a and P3b latencies in adults as compared to adolescents. Acute EtOH administration was also found to produce a robust dose‐dependent increase in the latency of the P3a and P3b components in adult animals exposed to EtOH vapor as adolescents and air exposed controls; however, larger acute EtOH‐induced increases in P3a and P3b latencies were seen in controls as compared to adolescent vapor exposed rats. Conclusions Adolescent rats have a less intense P3 latency response to acute EtOH administration when compared to adult rats. Exposure to chronic EtOH during adolescence can cause "retention" of the adolescent phenotype of reduced P3 latency sensitivity to EtOH.